Semi‐transparent frequency reconfigurable antenna with DGS. Issue 1 (1st December 2017) - Lim, M.C.; Rahim, S.K.A.; Hamid, M.R.; Soh, P.J.; Eteng, Aa
Abstract: In this letter, a semi‐transparent frequency reconfigurable antenna is proposed and investigated. This antenna is implemented on glass as a substrate, AgHT‐4 as a radiating element and copper as its ground plane to result in a semi‐transparent feature. A pair of PIN diodes is utilized as microwave switches along with a DC biasing circuit. This proposed antenna is fed by a CPW arrangement and introduces unequal E‐shaped Defected Ground Structure (DGS) on the ground plane for modification of the electrical length. The antenna exhibits a −10 dB impedance bandwidth from 3 to 6 GHz when PIN diodes are ON, and a resonance at 4.75 GHz when pin diodes are OFF. The proposed antenna is fabricated to validate its performance in terms of reflection coefficient and radiation pattern.